2023
DOI: 10.3389/fspor.2023.1058305
|View full text |Cite
|
Sign up to set email alerts
|

Sport-related concussion disclosure in women's rugby—A social identity approach

Abstract: IntroductionSport-related concussion (SRC) is a risk of collision sports such as women's rugby. To support appropriate SRC diagnosis and management, an understanding of the factors that encourage SRC disclosure is necessary. To date, research has focused on ascertaining individual player knowledge and attitudes towards SRC disclosure.MethodsWe chose to investigate the potential influence of group identification effects by examining the role of social identity on SRC disclosure in elite women's rugby. Seventeen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 88 publications
0
4
0
Order By: Relevance
“…Open channels of communication promote collaboration and enable the sharing of insights from multiple perspectives to make informed athlete-centred decisions, such as athletes’ RTP strategies. On the other hand, when communication breaks down, it can lead to increased misunderstandings and a risk of one-sided decision making [ 17 , 75 ]. The limited recognition of PDs’/PNs’ role by other team members in the event of injury has led to incidents where participants experienced closed communication channels, impacting their awareness of their athlete’s history with SRC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Open channels of communication promote collaboration and enable the sharing of insights from multiple perspectives to make informed athlete-centred decisions, such as athletes’ RTP strategies. On the other hand, when communication breaks down, it can lead to increased misunderstandings and a risk of one-sided decision making [ 17 , 75 ]. The limited recognition of PDs’/PNs’ role by other team members in the event of injury has led to incidents where participants experienced closed communication channels, impacting their awareness of their athlete’s history with SRC.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, nutrient absorption and energy availability to the brain may be facilitated, as reported anecdotally by PN [11] (see Figure 3), to support SRC healing and recovery. Effective communication and collaboration amongst backroom team practitioners and athletes are key mediators in establishing effective recovery strategies after injury diagnosis [17,75], especially after SRC. PDs/PNs know that differing levels of communication exist as part of working in a team and recognise that a "decent backroom team" [PN 5] needs internal collaboration to formulate and deliver suitable protocols to manage SRC recovery.…”
Section: Probioticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Themes of communication have been evidenced in previous research whereby coach communication may be a predictor of concussion disclosure to coaches or sports medicine staff in collegiate athletes ( 41 ). Meanwhile research in female rugby union identified poor communication as a mediator of injury disclosure vertically (from amateur to elite programs) and horizontally (across a club program) ( 42 ). This study also found that female athletes lacked access to allied healthcare provision; this has also been observed in previous literature on female Gaelic games athletes ( 19 , 43 ).…”
Section: Discussionmentioning
confidence: 99%